Performance Analysis of the 1 MW Rooftop Solar Power Generation System at the Karawang: Analisa Kinerja Sistem Pembangkit Listrik Tenaga Surya Atap 1 MW di Daerah Karawang - Prasetiya, Rizqullah Yoga; Adilla, Sulthon Alfa; Farid, Muhammad Farid Khol’ilmy; Hakim, Ermanu A.; Suhardi, Diding (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2024)
Electric energy is crucial for development, with Indonesia's projected electricity demand reaching 120 GW by 2025. The National Energy Policy emphasizes the development of renewable energy, particularly Solar Power Plants (PLTS), which have rapidly advanced with increased efficiency and reduced production costs. PLTS has become an attractive option, especially in areas with high solar intensity, for applications such as home lighting and vaccine storage. The target PLTS capacity is 400 MW by 2024. Despite growing popularity, challenges such as high initial costs and efficiency in unstable weather conditions remain. Research shows that environmental factors and shading can affect PLTS performance. This study analyzes the performance of a 1 MW PLTS system at a ceramic factory in Karawang using Global Solar Atlas and PVsyst for simulation and comparison with field data. Simulation results indicate optimal power production >90% with a performance ratio between 81.90% and 84.70%. The built PLTS shows a stable performance ratio above 79%, with power production differing by <10% compared to PVsyst simulation, demonstrating system reliability in actual operational conditions. This research underscores the importance of environmental factors in PLTS design and operation to achieve maximum efficiency.